Revitalizing Indonesian Tourism: Insights from Gunungkidul Regency's Communication Strategy - Shenja Nanta Asmara; Mufid Salim; Galant Nanta Adhitya; Rustono Farady Marta; Nunik Hariyanti; Fitrinanda An Nur (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Tourism is a crucial part of Indonesia's economy, thanks to the country's natural beauty and attractions. However, the COVID-19 pandemic has presented significant challenges to the sector, requiring innovative strategies to revive it. This study examines the communication strategy of the Gunungkidul Regency Tourism Office, focusing on how it navigates the complexities of the new normal era. The study uses a qualitative descriptive approach and centers on the Gunungkidul Regency Tourism Office. Data was gathered through observation and documentation of tourist sites and interviews with tourism officials, site management personnel, and tourists from June to July 2021. The study found that the Gunungkidul Regency Tourism Office diligently adopted key communication strategy phases, including audience profiling, message formulation, method selection, and media choice. They also provided fundamental components of tourism development, such as attraction, accessibility, amenities, and ancillary, to cater to tourist demands. The strategy emphasizes effective communication to engage diverse stakeholders, using audience segmentation and engagement and multimedia platforms to ensure maximal outreach and resonance. The findings highlight the importance of crisis communication best practices, audience segmentation, and evaluating tourism community resilience, which are essential for crafting a resilient and sustainable tourism ecosystem.